Primary vs delayed primary closure in patients undergoing lower limb amputation following trauma: A randomised control study. Issue 2 (20th December 2019) - Katiyar, Anand K.; Agarwal, Harshit; Priyadarshini, Pratyusha; Kumar, Abhinav; Kumar, Subodh; Gupta, Amit; Mishra, Biplab; Aggarwal, Richa; Soni, Kapil D.; Mathur, Purva; Sagar, Rajesh; Srivastava, Anurag; et al.
Abstract: Lower limb crush injury is a major source of mortality and morbidity in trauma patients. Complications, especially surgical site infections (SSIs) are a major source of financial burden to the institute and to the patient as it delays rehabilitation. As such, every possible attempt should be made to reduce any complications. We, thus, aimed to compare the outcomes in early vs delayed closure of lower extremity stumps in cases of lower limb crush injury requiring amputation, so as to achieve best possible outcome. A randomised controlled study was conducted in the Division of Trauma Surgery & Critical Care at Jai Prakash Narayan Apex Trauma Centre, All India Institute of Medical Sciences, New Delhi from 1 September 2018 to 30 June 2019 and included patients undergoing lower limb amputation below hip joint. Patients were randomised in two groups, in one group amputation stump was closed primarily, while in the second group delayed primary closure of stump was performed. We compared rate of SSI, length of hospital stay, and number of surgeries in both the groups. Fifty‐six patients with 63 amputation stumps were recruited in the study. Mean age of patients in the study was 34 years, of which about 95% patients were males. The most common mechanism of injury was road traffic injury in 66% of patients. Mean injury severity score was 12.28 and four patients had diabetes preoperatively. Total 63 extremities were randomised with 30 cases in group I and 33 cases in group II as per computer‐generated random number. Above knee amputations was commonest (57.14%) followed by below knee amputations (33.3%). Two patients died in the current study. In group I, In‐hospital infection was detected in 7 cases (23.3%) and in group II 9 cases (27.3%) had SSI during hospital admission ( P > .05). Mean hospital stay in group I was 10.32 ± 7.68 days and in group II was 11 ± 8.17 days ( P > .05). Road traffic injuries and train‐associated injuries are a major cause of lower limb crush injuries, leading to limb loss. Delayed primary closure of such wounds requires extra number of surgical interventions than primary closure. There is no difference in extra number of surgical interventions required in both the groups. Thus, primary closure can be safely performed in patients undergoing lower limb amputations following trauma, provided that a good lavage and wound debridement is performed.